Multi-omics analysis identifies LANCL2 as a potential biomarker for the diagnosis and prognosis of gastric cancer - Fang, Xidong; Liu, Mengxiao; Ren, Qian; Li, Renpeng; Wu, Guozhi; Yuan, Hao; Zheng, Ya; Gou, Xi; Wang, Yuping; Zhou, Yongning (Scientific reports, 2025)
Gastric cancer (GC) constitutes a significant global public health burden due to its high morbidity rates and poor prognosis, underscoring the critical need for identifying novel therapeutic targets and elucidating their mechanisms. As a key member of the lanthionine synthetase C-like enzyme family, LANCL2 has shown aberrant expression in multiple malignancies. However, its biological significance in GC remains unclear. To this end, a series of exploration and research were conducted. Through integrated analyses of multi-omics databases and experimental validation, LANCL2 was up-regulated in STAD at both mRNA and protein levels. Moreover, elevated LANCL2 is closely associated with poor prognosis, and the constructed nomogram exhibited reliable predictive performance for 1, 3, and 5-year overall survival (OS) in the GC cohort. In addition, the genetic alteration status of LANCL2 was associated with new neoplasm event post initial therapy indicator, MSIsensor score, tumor mutation burden (TMB), and survival prognosis. Functional enrichment analysis indicated that LANCL2 is primarily associated with the regulation of immune checkpoints, the cell cycle and DNA repair. Furthermore, the expression of LANCL2 displayed significant correlations with immune infiltration, m6A methylation, ferroptosis, tumor cell stemness and drug reactivity. Finally, in vitro studies confirmed that silencing or overexpression of LANCL2 can significantly influence the changes of proliferation and cell cycle of GC cells. Overall, this study indicated LANCL2 as a critical regulator in GC pathogenesis, and highlighted its potential as a prognostic biomarker for gastric cancer management.